Developing the information search system for selecting the moulds forming elements - Sotnik, S. V.; Nevliudova, V.; Malaya, I. (ХНУРЕ, 2017)
Today the information environment is highly developed, it enables collecting, processing, storing, distributing, searching and transferring of information. The need for automation of information activities and information resources management at all levels stipulates the demand for the development of information search systems. The subject matter of this research is the information search system for selecting the moulds forming elements. The aim of this work is to reduce the time for searching and determining the main parameters of the matrices, punches and characters by means of creating the information search system for selecting the moulds forming elements. To achieve this goal the following tasks should be solved: to review the main moulds forming elements and their technical parameters; to develop a search algorithm; to develop the database structure for selecting the moulds forming elements; to design the interface of the information search system. While solving the set tasks, the methodology of the systems analysis and modelling was used. The review the main objectives and characteristics of information search systems resulted in the development of the database logical structure which consists of 6 tables. The interface of the information search system was developed. It provides the “easy” and self-explanatory selection of moulds forming elements. Thus, the developed system includes information about the unique number of the forming elements; their type, name and properties; material and features of the quality of a workpiece surface; a workpiece kind and form to determine the nominal dimensions of forming elements. The use of the system enables reducing the time of searching and identifying forming the key technical parameters of forming elements as well as storing and manipulating the data about these elements.
Keywords: selection; interface; information